Positive electrode material precursor and preparation method thereof, lithium ion battery positive electrode material, lithium ion battery and electric equipment
By developing a positive electrode material precursor with a specific aspect ratio and structure, the problems of large resistance and insufficient reactivity of the positive electrode material of the lithium-ion battery during the Li+ migration process are solved, and a lithium-ion battery with high capacity and excellent circulation performance are achieved.
Patent Information
- Application Number
- CN202411746149.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-03-18
AI Technical Summary
The existing lithium-ion battery positive electrode materials have problems such as large resistance, insufficient reactivity and stress accumulation during the Li+ migration process, which affects its cycling performance and capacity.
A precursor of positive electrode material is developed, which consists of secondary particles, including a core layer and a shell layer. The average aspect ratio of primary particles in the shell layer is (1.5-8):1, the average aspect ratio of primary particles on the surface is (1-3):1, and the porosity of the core layer is 4-14%, and is prepared by co-precipitation reaction.
By optimizing the structure of the precursor of the positive electrode material, the Li+ diffusion resistance is reduced, the particle strength is improved, and the capacity and circulation performance of the material are enhanced.
Smart Images

Figure CN119637962A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium-ion batteries, and in particular to a positive electrode material precursor and a preparation method thereof, a lithium-ion battery positive electrode material, a lithium-ion battery, and electrical equipment. Background Art
[0002] Lithium-ion batteries are widely used in automotive power batteries due to their high specific capacity and fast charge and discharge characteristics. + The migration rate and reactive area inside the positive electrode material determine the specific capacity of the positive electrode. A small migration resistance of Li+ and a high migration rate are conducive to the capacity of the positive electrode. + When the positive electrode material migrates inside the positive electrode crystal and at the grain boundary, it will cause the volume of the positive electrode material lattice to expand and contract, and at the same time, stress accumulation will occur inside the crystal or at the grain boundary, thus affecting the cycle performance. Excellent positive electrode materials for lithium-ion batteries should have the following characteristics in structure and composition: high crystallinity to make Li + Small resistance during migration; suitable internal structure to facilitate the material's reaction activity and stress release; high particle strength to meet the structural stability of the material under high voltage conditions and the strength requirements during processing; low Ni / Co content and high Mn content to reduce material costs. The structural characteristics of lithium-ion battery positive electrode materials mainly depend on the precursor of the positive electrode material, such as its porosity, main element ratio, particle arrangement, particle geometric size, particle strength, etc. The structure of the positive electrode material precursor will be retained to a certain extent during the sintering process of the positive electrode material. Therefore, the development of a lithium-ion positive electrode material precursor with a suitable internal structure and a reasonable elemental composition is of great significance to obtain high-performance positive electrode materials. Summary of the invention
[0003] The purpose of the present invention is to provide a positive electrode material precursor and a preparation method thereof, a lithium ion battery positive electrode material, a lithium ion battery and electrical equipment, aiming to solve at least one of the above-mentioned technical problems in the prior art.
[0004] In order to achieve the above-mentioned purpose, the first aspect of the present invention provides a positive electrode material precursor, which includes secondary particles composed of primary particles, and the secondary particles include a core layer and a shell layer. In the cross-section of the secondary particles, the average aspect ratio of the shell layer primary particles is (1.5~8):1, and in the surface of the secondary particles, the average aspect ratio of the primary particles is (1~3):1.
[0005] Preferably, the ratio of the thickness of the shell layer in the secondary particle to the radius of the secondary particle is 0.55 to 0.95.
[0006] Preferably, the core layer of the secondary particles is distributed in a network shape, and the shell layer is distributed in a radial shape.
[0007] Preferably, the porosity of the core layer in the secondary particles is 4-14%.
[0008] Preferably, the chemical formula of the positive electrode material precursor is Ni x Co y Mn z M t (OH) 2 , wherein 0.4≤x<1, 0≤y≤0.2, 0.2≤z≤0.6, 0≤t≤0.05, x+y+z+t=1, and M is selected from at least one of W, Al, Zr, Si, Mg, Mo, B, Sr and Ta.
[0009] According to a preferred embodiment, the cathode material precursor satisfies one or more of the following conditions:
[0010] a. In the cross section of the secondary particles, the average aspect ratio of the primary shell particles is (2 to 6): 1;
[0011] b. In the surface of the secondary particles, the average aspect ratio of the primary particles is (1.05-2.1):1;
[0012] c. The ratio of the thickness of the shell layer in the secondary particles to the radius of the secondary particles is 0.6 to 0.9;
[0013] d. The porosity of the core layer of the secondary particles is 5-12%;
[0014] e. The chemical formula of the positive electrode material precursor is Ni x Co y Mn z M t (OH) 2 , where 0.4≤x≤0.7, 0≤y≤0.2, 0.2≤z≤0.6, 0≤t≤0.05, x+y+z+t=1;
[0015] f. The particle size D50 of the positive electrode material precursor is 2-15 μm, preferably 3-7 μm.
[0016] A second aspect of the present invention provides a method for preparing a cathode material precursor as described in the first aspect, the preparation method comprising the following steps:
[0017] preparing a metal salt solution, a complexing agent solution and a precipitant solution;
[0018] mixing the complexing agent solution, the precipitant solution and water to form a base solution;
[0019] Under the protection of inert gas, the metal salt solution, the complexing agent solution and the precipitant solution are introduced into the base liquid to carry out a coprecipitation reaction.
[0020] Preferably, the preparation method satisfies one or more of the following conditions:
[0021] A: the metal salt solution is selected from one or more of a nickel sulfate solution, a cobalt sulfate solution, a manganese sulfate solution and a salt solution of a doping element M;
[0022] B: The mass concentration of metal ions in the metal salt solution is 100 to 140 g / L, preferably 110 to 130 g / L, and more preferably 120 g / L;
[0023] C: The complexing agent solution is selected from an ammonia solution, and preferably, the mass fraction of the complexing agent solution is 0.1%-30%;
[0024] D: The precipitant solution is selected from sodium hydroxide solution, and preferably, the mass fraction of the precipitant solution is 10%-30%;
[0025] E: the pH value of the base liquid is 10.5-12.0, and / or the mass concentration of ammonia water in the base liquid is 5-13.5 g / L;
[0026] F: The pH value of the coprecipitation reaction sequentially experiences a pH drop phase and a pH plateau phase;
[0027] G: The reaction time of the coprecipitation reaction in the pH drop period is 15-30 hours;
[0028] H: the pH value of the pH plateau phase is 10.0-10.5, and / or the reaction time of the coprecipitation reaction in the pH plateau phase is 22-39 hours;
[0029] I: The stirring speed of the coprecipitation reaction is 300-600 r / min, and / or the temperature of the coprecipitation reaction is 55-75° C., and / or the mass concentration of ammonia water in the coprecipitation reaction is 5-13.5 g / L.
[0030] A third aspect of the present invention provides a positive electrode material for a lithium ion battery, wherein the raw material of the positive electrode material for a lithium ion battery includes the positive electrode material precursor as described in the first aspect.
[0031] A fourth aspect of the present invention provides a lithium ion battery, comprising the lithium ion battery positive electrode material as described in the third aspect.
[0032] A fifth aspect of the present invention provides an electrical device, comprising the lithium-ion battery as described in the fourth aspect.
[0033] Compared with the prior art, the technical solution provided by the present invention has at least the following advantages:
[0034] The positive electrode material precursor provided by the present invention contains primary particles with a suitable aspect ratio, which is not only beneficial to reduce Li + The positive electrode material precursor provided by the present invention is applied to a lithium ion battery, and the obtained lithium ion battery has both high capacity and excellent cycle performance.
[0035] The preparation method of the positive electrode material precursor provided by the present invention is simple, highly operable, and is conducive to large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 is a CP diagram of the cathode material precursor prepared in Example 1 of the present invention;
[0037] Figure 2 is a SEM image of the cathode material precursor prepared in Example 1 of the present invention;
[0038] Figure 3 is a CP diagram of the cathode material precursor prepared in Example 5 of the present invention;
[0039] Figure 4 is a SEM image of the cathode material precursor prepared in Example 5 of the present invention;
[0040] Figure 5 is a CP diagram of the cathode material precursor prepared in Example 7 of the present invention;
[0041] Figure 6 is a SEM image of the positive electrode material precursor prepared in Example 7 of the present invention;
[0042] Figure 7 It is a CP diagram of the positive electrode material precursor prepared in Example 12 of the present invention. DETAILED DESCRIPTION
[0043] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0044] It should be noted that, in various aspects of the present invention, for the same components or terms in various aspects, the present invention is described only once in one aspect without repeated description, which should not be understood by those skilled in the art as a limitation of the present invention.
[0045] As used herein:
[0046] "Prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.
[0047] The conjunction "consisting of excludes any unspecified element, step, or component. If used in a claim, this phrase renders the claim closed-ended so that it does not include materials other than those described, except for conventional impurities associated therewith. When the phrase "consisting of" appears in a clause of the body of a claim rather than immediately following the subject matter, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.
[0048] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including ranges "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described in this article, unless otherwise stated, the range is intended to include its end values and all integers and fractions within the range.
[0049] In these examples, parts and percentages are by mass unless otherwise indicated.
[0050] "Parts by mass" refers to the basic unit of measurement for expressing the mass ratio of multiple components. 1 part can represent any unit mass, such as 1g or 2.689g. If we say that the mass of component A is a parts and the mass of component B is b parts, it means the ratio of the mass of component A to the mass of component B is a:b. Alternatively, it means that the mass of component A is aK and the mass of component B is bK (K is an arbitrary number, indicating a multiple factor). It should not be misunderstood that, unlike the mass parts, the sum of the mass of all components is not limited to 100 parts.
[0051] "And / or" is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B).
[0052] The cross section of a sphere refers to a plane figure obtained by cutting a sphere with a plane. In the present invention, unless otherwise specified, the secondary particle cross section and the secondary particle profile have the same meaning, which refers to a plane figure formed by the cutting plane passing through the center of the sphere or the center of the particle.
[0053] In the present invention, unless otherwise specified, the core layer and the shell layer of the secondary particles are distinguished in the following manner: the arrangement of the primary particles of the core layer and the shell layer is obviously different. For example, the primary particles of the core layer are distributed in a network shape, and the primary particles of the shell layer are distributed radially.
[0054] In the present invention, unless otherwise specified, the clear boundaries that can be identified in the CP diagram (including but not limited to clear and complete cracks, the boundary between the deep and shallow shadows, the boundary between different textures, etc.) are used as the boundaries of the primary particles in the cross section. Specifically, based on the above identification principle, in the cross section of the secondary particles described in the present invention, the primary particles in the shell layer may be a single primary particle or a primary particle cluster containing multiple particles.
[0055] In the present invention, unless otherwise specified, the method for calculating the radius of the secondary particle and the thickness of the shell layer in the secondary particle is as follows: take a cross-sectional view of the secondary particle, 1) fit the cross-section into the closest circle according to the rule of equal area through image J software, and obtain the center and diameter D of the secondary particle (the radius of the secondary particle R=D / 2 is calculated accordingly), 2) fit the core layer in the cross-section into the closest circle according to the rule of equal area through image J software, and obtain the center and diameter d of the core layer (the radius of the core layer r=d / 2 is calculated accordingly), 3) calculate the thickness H=Rr of the shell layer of the secondary particle.
[0056] In the present invention, the method for calculating the ratio of the shell thickness in the secondary particles of the positive electrode material precursor to the radius of the secondary particles is: within the particle size range of D50±2μm, 10 secondary particles are randomly selected, and the ratio of the shell thickness H (Rr) of each secondary particle to the radius R of the secondary particle is first calculated, and then the average value of the above ratios of the 10 secondary particles is calculated, which is the ratio of the shell thickness of the secondary particles of the positive electrode material precursor to the radius of the secondary particles.
[0057] In the present invention, unless otherwise specified, the method for calculating the aspect ratio of the shell primary particle in the cross section of a single secondary particle is: 1) obtaining the length and width of a single primary particle in the shell layer of the cross section of the secondary particle, and the testing method is: using NanoMeasurer software to measure the length and width of the primary particles on the surface of the secondary particle in the CP diagram with a magnification of 10000-100000 times, the longest axis of a single primary particle is regarded as its length, and the short axis measured perpendicular to the midpoint of the longest axis is regarded as its width; 2) calculating the ratio of length to width, which is the aspect ratio of the primary particle; 3) calculating the average of the aspect ratios of all identifiable primary particles in the shell layer of the CP diagram, which is the aspect ratio of the shell primary particle in the cross section of the secondary particle.
[0058] In the present invention, unless otherwise specified, the method for calculating the average aspect ratio of the shell primary particles in the cross section of the secondary particles of the positive electrode material precursor is: within the particle size range of D50±2μm, 10 secondary particles are randomly selected, and the aspect ratio of the shell primary particles in the cross section of each secondary particle is calculated. Then, the average value of the ratio of the 10 secondary particles is calculated, which is the average aspect ratio of the shell primary particles in the cross section of the secondary particles of the positive electrode material precursor.
[0059] In the present invention, unless otherwise specified, the method for calculating the aspect ratio of the primary particles on the surface of the secondary particles is: 1) obtaining the average length and average width of a single primary particle on the surface of the positive electrode material precursor, and the testing method is: using NanoMeasurer software to measure the length and width of the primary particles on the surface of the secondary particles in the SEM image with a magnification of 10000-100000 times, the longest axis of a single primary particle is regarded as its length, and the short axis measured perpendicular to the midpoint of the longest axis is regarded as its width; 2) calculating the ratio of length to width, which is the aspect ratio of the primary particle on the surface of the secondary particle; 3) calculating the average of the aspect ratios of all identifiable primary particles in the SEM image, which is the aspect ratio of the primary particles on the surface of the secondary particles.
[0060] In the present invention, unless otherwise specified, the method for calculating the average aspect ratio of the primary particles on the surface of the secondary particles of the positive electrode material precursor is: within the particle size range of D50±2μm, 10 secondary particles are randomly selected, the aspect ratio of the primary particles on the surface of each secondary particle is calculated, and then the average value of the ratio of the 10 secondary particles is calculated, which is the average aspect ratio of the primary particles on the surface of the secondary particles of the positive electrode material precursor.
[0061] In the present invention, the porosity of the core layer in the secondary particles is measured by porosity statistical software.
[0062] In the present invention, the morphology of the cathode material precursor is characterized by a scanning electron microscope (SEM); the internal structure of the cathode material precursor is characterized by ion beam milling (CP) and a scanning electron microscope.
[0063] As mentioned above, the first aspect of the present invention provides a positive electrode material precursor, which includes secondary particles composed of primary particles, the secondary particles include a core layer and a shell layer, and in the cross-section of the secondary particles, the average aspect ratio of the shell layer primary particles is (1.5~8):1, and in the surface of the secondary particles, the average aspect ratio of the primary particles is (1~3):1.
[0064] In the present invention, by controlling the aspect ratio of the primary particles in the secondary particle shell layer and the aspect ratio of the primary particles in the surface of the secondary particles in the positive electrode material precursor within the above range, the obtained positive electrode material precursor is applied to the positive electrode material of a lithium ion battery, so that the overall capacity and cycle performance of the positive electrode material are better.
[0065] Preferably, the ratio of the thickness of the shell layer in the secondary particle to the radius of the secondary particle is 0.55-0.95, for example, it can be 0.55, 0.6, 0.7, 0.8, 0.9, 0.95 or any value between 0.55 and 0.95, and in the present invention, it is preferably 0.6-0.9.
[0066] Preferably, the core layer of the secondary particles is distributed in a network shape, and the shell layer is distributed in a radial shape.
[0067] In some embodiments of the present invention, the primary particles of the shell are radially distributed, so the thickness of the shell is close to the length of the primary particles, and the primary particles constituting the secondary particles not only have a specific range of aspect ratios (the average aspect ratio of the primary particles in the shell of the secondary particles is (1.5-8):1 and the average aspect ratio of the primary particles on the surface of the secondary particles is (1-3):1), but also the overall size of the primary particles is larger than that of the secondary particles (the ratio of the thickness of the shell in the secondary particles to the radius of the secondary particles is 0.55-0.95). The secondary particle positive electrode material precursor composed of primary particles with the above characteristics not only has better overall capacity and cycle performance, but also has higher particle strength.
[0068] In some embodiments of the present invention, the core layer network structure and shell layer radial structure of the secondary particles in the positive electrode material precursor enable it to be used in the positive electrode material of lithium-ion batteries, so that the capacity of the positive electrode material of lithium-ion batteries can be better exerted, and it is beneficial to balance the grain volume change and stress release during the charge and discharge process.
[0069] Preferably, the porosity of the core layer in the secondary particles is 4-14%, for example, it can be 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14% or any value between 4-14%, and the present invention preferably is 5-12%.
[0070] In some embodiments of the present invention, the core layer network structure of the secondary particles in the positive electrode material precursor has more grain boundaries, which, combined with the porosity of the core layer in the secondary particles, makes the positive electrode material precursor have better activity, which is beneficial to the overall particle strength and cycle performance of the material.
[0071] Preferably, the chemical formula of the positive electrode material precursor is Ni x Co y Mn z M t (OH) 2 , wherein 0.4≤x<1, 0≤y≤0.2, 0.2≤z≤0.6, 0≤t≤0.05, x+y+z+t=1, and M is selected from at least one of W, Al, Zr, Si, Mg, Mo, B, Sr and Ta.
[0072] In some embodiments, in the cross-section of the secondary particles, the average aspect ratio of the shell primary particles is (2-6):1, for example, it can be (2.0-2.5):1, (2.5-3.0):1, (3.0-3.5):1, (3.5-4.0):1, (4.0-4.5):1, (4.5-5.0):1, (5.0-5.5):1, (5.5-6.0):1 or any ratio between (2-6):1.
[0073] In some embodiments, in the cross-section of the secondary particles, the average aspect ratio of the shell primary particles is (2.5-3.0):1, (3.0-3.5):1, (3.5-4.0):1, (4.0-4.5):1 or (4.5-5.0):1, and the ratio of the thickness of the shell layer in the secondary particles to the radius of the secondary particles is 0.60-0.65, 0.65-0.70, 0.70-0.75, 0.75-0.80 or 0.80-0.85.
[0074] In some embodiments, in the surface of the secondary particles, the average aspect ratio of the primary particles is (1.05-2.1):1, for example, it can be (1.05-1.2):1, (1.2-1.4):1, (1.4-1.6):1, (1.60-1.80):1, (1.8-2.0):1, (2.0-2.1):1 or any ratio between (1.05-2.1):1.
[0075] In some embodiments, the chemical formula of the positive electrode material precursor is Ni x Co y Mn z M t (OH) 2 , where 0.4≤x≤0.7, 0≤y≤0.2, 0.2≤z≤0.6, 0≤t≤0.05, x+y+z+t=1, for example, 0.4≤x≤0.65, 0.4≤x≤0.55, 0.5≤x≤0.55, 0.5≤x≤0.7 or 0.5≤x≤0.65.
[0076] In some embodiments, the particle size D50 of the positive electrode material precursor is 2-15 μm, for example, it can be 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm or any value between 2-15 μm, preferably 3-7 μm.
[0077] It should be noted that the particle size D50 in the present invention is the particle size corresponding to when the cumulative particle size distribution percentage of the positive electrode material precursor reaches 50%.
[0078] A second aspect of the present invention provides a method for preparing a cathode material precursor as described in the first aspect, the preparation method comprising the following steps:
[0079] preparing a metal salt solution, a complexing agent solution and a precipitant solution;
[0080] mixing the complexing agent solution, the precipitant solution and water to form a base solution;
[0081] Under the protection of inert gas, the metal salt solution, the complexing agent solution and the precipitant solution are introduced into the base liquid to carry out a coprecipitation reaction.
[0082] In some embodiments, the coprecipitation reaction is carried out in a reactor, and when the upper limit of the reactor volume is reached, concentration is started to allow the reactor to be used continuously.
[0083] The present invention has no special requirements for the concentration conditions, and those skilled in the art can select them as needed.
[0084] The present invention has no special requirements on the type of water, and those skilled in the art can select it as needed. Exemplarily, the water is pure water.
[0085] The present invention has no special requirements on the type of the inert gas, and those skilled in the art can select it as needed. Exemplarily, the inert gas is nitrogen.
[0086] In some embodiments, the metal salt solution is selected from one or more of a nickel sulfate solution, a cobalt sulfate solution, a manganese sulfate solution, and a salt solution of a doping element M.
[0087] In some embodiments, the mass concentration of metal ions in the metal salt solution is 100-140 g / L, for example, it can be 100 g / L, 110 g / L, 120 g / L, 130 g / L, 140 g / L or any value between 100 and 140 g / L, preferably 110-130 g / L, and more preferably 120 g / L.
[0088] In some embodiments, the complexing agent solution is selected from an aqueous ammonia solution.
[0089] In some embodiments, the mass fraction of the complexing agent solution is 0.1%-30%, for example, it can be 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30% or any value in the range of 0.1%-30%.
[0090] In some embodiments, the precipitant solution is selected from sodium hydroxide solution.
[0091] In some embodiments, the mass fraction of the precipitant solution is 10%-30%, for example, it can be 10%, 20%, 30% or any value between 10%-30%.
[0092] In some embodiments, the pH value of the base solution is 10.5-12.0, for example, it can be 10.5, 11, 11.5 or any value between 10.5-12.0;
[0093] Optionally, the pH value of the base solution is 10.5-11.5.
[0094] In some embodiments, the mass concentration of aqueous ammonia in the base solution is 5-13.5 g / L, for example, it can be 5 g / L, 6 g / L, 7 g / L, 8 g / L, 9 g / L, 10 g / L, 11 g / L, 12 g / L, 13 g / L, 13.5 g / L or any value between 5-13.5 g / L;
[0095] Optionally, the mass concentration of ammonia water in the base liquid is 8-10 g / L.
[0096] In some embodiments, the pH value of the co-precipitation reaction sequentially undergoes a pH drop phase and a pH plateau phase.
[0097] In some embodiments, the reaction time of the coprecipitation reaction in the pH decrease period is 15-30 hours, for example, it can be 15 hours, 16 hours, 17 hours, 18 hours, 19 hours, 20 hours, 21 hours, 22 hours, 23 hours, 24 hours, 25 hours, 26 hours, 27 hours, 27 hours, 28 hours, 29 hours, 30 hours or any value between 15-30 hours.
[0098] In some embodiments, the pH value of the pH plateau phase is 10.0-10.5.
[0099] In some embodiments, the reaction time of the coprecipitation reaction in the pH plateau phase is 22-39 hours, for example, it can be 22 hours, 23 hours, 24 hours, 25 hours, 26 hours, 27 hours, 27 hours, 28 hours, 29 hours, 30 hours, 31 hours, 32 hours, 33 hours, 34 hours, 35 hours, 36 hours, 37 hours, 38 hours, 39 hours or any value between 22-39 hours.
[0100] In some embodiments, the stirring speed of the coprecipitation reaction is 300-600 r / min, for example, 300 r / min, 400 r / min, 500 r / min, 600 r / min or any value between 300-600 r / min.
[0101] In some embodiments, the coprecipitation reaction temperature is 55-75°C, for example, 55°C, 60°C, 65°C, 70°C, 75°C or any value between 55-75°C.
[0102] In some embodiments, the mass concentration of aqueous ammonia in the coprecipitation reaction is 5-13.5 g / L, for example, it can be 5 g / L, 6 g / L, 7 g / L, 8 g / L, 9 g / L, 10 g / L, 11 g / L, 12 g / L, 13 g / L, 13.5 g / L or any value between 5-13.5 g / L.
[0103] The preparation method of the positive electrode material precursor of the present invention may also include post-processing means known in the art such as centrifugation, washing, and demagnetization, so as to obtain the positive electrode material precursor with better quality. The present invention will not be repeated here, and those skilled in the art should not understand it as a limitation of the present invention.
[0104] As mentioned above, the third aspect of the present invention provides a positive electrode material for a lithium ion battery, wherein the raw material of the positive electrode material for a lithium ion battery includes the positive electrode material precursor as described in the first aspect.
[0105] The present invention has no particular limitation on the method for preparing a positive electrode material for a lithium ion battery using the positive electrode material precursor provided by the present invention, and those skilled in the art can select the method according to the technical means known in the art. However, in order to obtain a positive electrode material for a lithium ion battery with better electrochemical performance, the present invention preferably uses the following method to prepare the positive electrode material for a lithium ion battery.
[0106] According to a preferred specific embodiment, the method for preparing the positive electrode material of a lithium ion battery comprises:
[0107] Evenly mixing the positive electrode material precursor and the lithium-containing compound to obtain a mixed material;
[0108] The mixed material is sintered under air atmosphere to obtain the positive electrode material for lithium-ion battery.
[0109] The preparation method of the lithium ion battery positive electrode material of the present invention may also include cooling, crushing, screening and other post-processing means known in the art to obtain the lithium ion battery positive electrode material with better quality. The present invention will not be repeated here, and those skilled in the art should not be understood as limiting the present invention.
[0110] In some embodiments, the lithium-containing compound is Li 2 CO 3 and / or LiOH.
[0111] In some embodiments, the sintering conditions include: heating to 800-1000°C at a heating rate of 5-10°C / h, for example, 800, 850, 900°C, 1000°C or any value between 800-1000°C; sintering time is 10-15h, for example, 10h, 11h, 12h, 13h, 14h, 15h or any value between 10-15h.
[0112] In the present invention, the sintering time includes the time required for heating.
[0113] In some embodiments, the molar ratio of the positive electrode material precursor to the lithium-containing compound is 1:1.05-1.10.
[0114] As mentioned above, the fourth aspect of the present invention provides a lithium-ion battery, comprising the lithium-ion battery positive electrode material as described in the third aspect.
[0115] According to a preferred specific embodiment, the lithium ion battery is obtained by the following preparation method:
[0116] (1) The above-mentioned lithium-ion battery positive electrode material, conductive carbon black, and binder PVDF (polyvinylidene fluoride) are mixed into a slurry at a ratio of 8:1:1, and the slurry is evenly coated on an aluminum foil with a length and width of 2 cm×1 cm to prepare a positive electrode sheet.
[0117] (2) Assemble the battery case, positive electrode sheet, negative electrode sheet (metal lithium sheet), diaphragm, spring, gasket and electrolyte into a button battery in a vacuum glove box.
[0118] The present invention has no special requirements on the type of the diaphragm, and those skilled in the art can select one according to needs.
[0119] As mentioned above, the fifth aspect of the present invention provides an electrical device, comprising the lithium-ion battery as described in the fourth aspect.
[0120] The present invention will be described in detail below by way of examples. In the following examples, unless otherwise specified, the raw materials are all commercially available.
[0121] Nickel sulfate solution: The mass concentration of nickel ions is 120g / L.
[0122] Cobalt sulfate solution: The mass concentration of cobalt ions is 120g / L.
[0123] Manganese sulfate solution: The mass concentration of manganese ions is 120g / L.
[0124] Aluminum sulfate solution: mass concentration is 0.5g / L.
[0125] Sodium tungstate solution: mass concentration is 0.2g / L.
[0126] Complexing agent solution: 10.5% ammonia solution by mass.
[0127] Precipitant solution: 20.5% sodium hydroxide solution by mass.
[0128] Diaphragm: The model is PE double-layer ceramic diaphragm.
[0129] Electrolyte: ethylene carbonate solution containing lithium hexafluorophosphate (the concentration of lithium hexafluorophosphate is 1 mol / L): dimethyl carbonate (DMC): ethyl methyl carbonate (EMC), volume ratio = 1:1:1.
[0130] Example 1
[0131] Prepare a chemical formula Ni 0.50 Co 0.10 Mn 0.40 (OH) 2 , the positive electrode material precursor with a particle size D50 of 3.3 μm, and the specific preparation method thereof is as follows:
[0132] ①Raw material preparation:
[0133] Prepare a metal salt solution: mix nickel sulfate solution, cobalt sulfate solution, manganese sulfate solution and pure water to obtain a metal salt solution, control the molar ratio of Ni:Co:Mn in the metal salt solution to be 50.0:10.0:40.0, and the sum of the mass concentrations of nickel ions, cobalt ions and manganese ions to be 120 g / L;
[0134] Preparation of base liquid: In a reaction kettle, sodium hydroxide solution, ammonia solution and pure water are mixed to form a base liquid, the pH of the base liquid is controlled to be 11.50, the mass concentration of ammonia water in the base liquid is 10.0 g / L, the temperature of the reaction kettle is raised to 65°C, and the stirring speed is controlled at 450 r / min;
[0135] ② Coprecipitation reaction
[0136] Under nitrogen protection, a metal salt solution (with a flow rate of 20% / h of the volume of the reactor), a sodium hydroxide solution (with a flow rate of 8.0% / h of the volume of the reactor) and an ammonia solution (with a flow rate of 0.60% / h of the volume of the reactor) are introduced into the base liquid to carry out a coprecipitation reaction to obtain a slurry;
[0137] The actual pH value during the coprecipitation reaction was controlled so that the pH value gradually decreased from 11.50 (pH decline period) to 10.00 and remained unchanged (pH plateau period);
[0138] The reaction time of the pH drop period is 15h, the pH drop rate in the pH drop period is 0.05-0.15 / h (the pH drop in the pH drop period is not a uniform drop, the drop rate fluctuates within this range, and the pH is controlled to finally drop to the pH plateau period), and the reaction time of the pH plateau period is 25h;
[0139] The mass concentration of ammonia water during the coprecipitation reaction was 10.0 g / L;
[0140] During the coprecipitation reaction, when the upper limit of the reactor volume is reached, concentration begins, and the stirring speed of the coprecipitation reaction is gradually reduced from 450 r / min to 300 r / min.
[0141] ③ Post-treatment: The slurry is filtered, washed, dried, sieved, and demagnetized in sequence to obtain a slurry having a chemical formula of Ni 0.50 Co 0.10 Mn 0.40 (OH) 2 The cathode material precursor (its CP diagram is as follows Figure 1 As shown in the SEM images Figure 2 shown).
[0142] pass Figure 1 and Figure 2It can be seen that in the positive electrode material precursor prepared in Example 1, the core layer of the secondary particles is distributed in a network shape, and the shell layer is distributed in a radial shape.
[0143] Example 2
[0144] Prepare a chemical formula Ni 0.40 Co 0.05 Mn 0.55 (OH) 2 , a positive electrode material precursor with a particle size D50 of 5.7μm.
[0145] This embodiment is carried out in a similar manner to that of Embodiment 1, except that:
[0146] In step ①, the molar ratio of Ni:Co:Mn in the metal salt solution is 40.0:5.0:55.0;
[0147] In step ②, the reaction time of the pH drop period is 15 hours, the pH value decrease rate in the pH drop period is 0.05-0.15 / h, and the reaction time of the pH plateau period is 30 hours;
[0148] During the coprecipitation reaction, when the upper limit of the reactor volume is reached, concentration begins, and the rest remain unchanged;
[0149] A positive electrode material precursor is prepared.
[0150] Example 3
[0151] Prepare a chemical formula Ni 0.65 Co 0.05 Mn 0.30 (OH) 2 , a positive electrode material precursor with a particle size D50 of 2.8μm.
[0152] This embodiment is carried out in a similar manner to that of Embodiment 1, except that:
[0153] In step ①, the molar ratio of Ni:Co:Mn in the metal salt solution is 65.0:5.0:30.0;
[0154] In step ②, the reaction time of the pH drop period is 15 hours, the pH value decrease rate in the pH drop period is 0.05-0.15 / h, and the reaction time of the pH plateau period is 22 hours;
[0155] During the coprecipitation reaction, when the upper limit of the reactor volume is reached, concentration begins, and the rest remain unchanged;
[0156] A positive electrode material precursor is prepared.
[0157] Example 4
[0158] Prepare a chemical formula Ni 0.55 Mn 0.45 (OH) 2 , a positive electrode material precursor with a particle size D50 of 6.9μm.
[0159] This embodiment is carried out in a similar manner to that of Embodiment 1, except that:
[0160] In step ①, the metal salt solution does not contain Co, the molar ratio of Ni:Mn in the metal salt solution is controlled to be 55.0:45.0, and the sum of the mass concentrations of nickel ions and manganese ions is 120 g / L;
[0161] In step ②, the reaction time of the pH drop period is 15 hours, the pH value decrease rate in the pH drop period is 0.05-0.15 / h, and the reaction time of the pH plateau period is 36 hours;
[0162] During the coprecipitation reaction, when the upper limit of the reactor volume is reached, concentration begins, and the rest remain unchanged;
[0163] A positive electrode material precursor is prepared.
[0164] Example 5
[0165] Prepare a chemical formula Ni 0.40 Co 0.049 Mn 0.55 W 0.001 (OH) 2 The specific preparation method of the positive electrode material precursor with a particle size D50 of 3.7 μm is as follows:
[0166] Prepare a metal salt solution: mix nickel sulfate solution, cobalt sulfate solution, manganese sulfate solution and pure water to obtain a metal salt solution, control the molar ratio of Ni:Co:Mn in the metal salt solution to be 40.0:5.0:55.0, and the sum of the mass concentrations of nickel ions, cobalt ions and manganese ions to be 120 g / L;
[0167] Preparation of base liquid: In a reaction kettle, sodium hydroxide solution, ammonia solution and pure water are mixed to form a base liquid, the pH of the base liquid is controlled to be 11.50, the mass concentration of ammonia water in the base liquid is 10.0 g / L, the temperature of the reaction kettle is raised to 65°C, and the stirring speed is controlled at 450 r / min;
[0168] ② Coprecipitation reaction
[0169] Under nitrogen protection, a metal salt solution (with a flow rate of 20% / h of the volume of the reactor), a sodium tungstate solution (with a flow rate of 5% / h of the volume of the reactor), a sodium hydroxide solution (with a flow rate of 8.0% / h of the volume of the reactor) and an ammonia solution (with a flow rate of 0.60% / h of the volume of the reactor) are introduced into the bottom liquid to carry out a coprecipitation reaction to obtain a slurry;
[0170] The actual pH value during the coprecipitation reaction was controlled so that the pH value gradually decreased from 11.50 (pH decline period) to 10.00 and remained unchanged (pH plateau period);
[0171] The reaction time of pH drop period was 15h, the pH value decrease rate in pH drop period was 0.05-0.15 / h, and the reaction time of pH plateau period was 27h;
[0172] The mass concentration of ammonia water during the coprecipitation reaction was 10.0 g / L;
[0173] During the coprecipitation reaction, when the upper limit of the reactor volume is reached, concentration begins, and the rest remain unchanged;
[0174] Prepare the positive electrode material precursor (its CP diagram is as follows Figure 3 As shown in the SEM images Figure 4 shown).
[0175] pass Figure 3 and Figure 4 It can be seen that in the positive electrode material precursor prepared in Example 5, the core layer of the secondary particles is distributed in a network shape, and the shell layer is distributed in a radial shape.
[0176] Example 6
[0177] Prepare a chemical formula Ni 0.40 Co 0.049 Mn 0.55 Al 0.001 (OH) 2 , the positive electrode material precursor with a particle size D50 of 4.1 μm, and the specific preparation method thereof is as follows:
[0178] Prepare a metal salt solution: mix nickel sulfate solution, cobalt sulfate solution, manganese sulfate solution and pure water to obtain a metal salt solution, control the molar ratio of Ni:Co:Mn in the metal salt solution to be 40.0:5.0:55.0, and the sum of the mass concentrations of nickel ions, cobalt ions and manganese ions to be 120 g / L;
[0179] Preparation of base liquid: In a reaction kettle, sodium hydroxide solution, ammonia solution and pure water are mixed to form a base liquid, the pH of the base liquid is controlled to be 11.50, the mass concentration of ammonia water in the base liquid is 10.0 g / L, the temperature of the reaction kettle is raised to 65°C, and the stirring speed is controlled at 450 r / min;
[0180] ② Coprecipitation reaction
[0181] Under nitrogen protection, a metal salt solution (with a flow rate of 20% / h of the volume of the reactor), an aluminum sulfate solution (with a flow rate of 5% / h of the volume of the reactor), a sodium hydroxide solution (with a flow rate of 8.0% / h of the volume of the reactor) and an ammonia solution (with a flow rate of 0.60% / h of the volume of the reactor) are introduced into the base liquid to carry out a coprecipitation reaction to obtain a slurry;
[0182] The actual pH value during the coprecipitation reaction was controlled so that the pH value gradually decreased from 11.50 (pH decline period) to 10.00 and remained unchanged (pH plateau period);
[0183] The reaction time of pH drop period was 15h, the pH value decrease rate in pH drop period was 0.05-0.15 / h, and the reaction time of pH plateau period was 28h;
[0184] The mass concentration of ammonia water during the coprecipitation reaction was 10.0 g / L;
[0185] During the coprecipitation reaction, when the upper limit of the reactor volume is reached, concentration begins, and the rest remain unchanged;
[0186] A positive electrode material precursor is prepared.
[0187] Example 7
[0188] Prepare a chemical formula Ni 0.50 Co 0.10 Mn 0.40 (OH) 2 , a positive electrode material precursor with a particle size D50 of 3.6μm.
[0189] This embodiment is carried out in a similar manner to that of Embodiment 1, except that:
[0190] In step ①, the pH of the base solution is controlled to be 11.00;
[0191] In step ②, the reaction time of the pH drop period is 18 hours, the pH value decrease rate in the pH drop period is 0.05-0.10 / h, and the reaction time of the pH plateau period is 25 hours;
[0192] During the coprecipitation reaction, when the upper limit of the reactor volume is reached, concentration begins, and the rest remain unchanged;
[0193] Prepare the positive electrode material precursor (its CP diagram is as follows Figure 5 As shown in the SEM images Figure 6 shown).
[0194] pass Figure 5 and Figure 6 It can be seen that in the positive electrode material precursor prepared in Example 7, the core layer of the secondary particles is distributed in a network shape, and the shell layer is distributed in a radial shape.
[0195] Example 8
[0196] Prepare a chemical formula Ni 0.50 Co 0.10 Mn 0.40 (OH) 2 , a positive electrode material precursor with a particle size D50 of 5.9μm.
[0197] This embodiment is carried out in a similar manner to that of Embodiment 1, except that:
[0198] In step ②, the flow rate of the metal salt solution is 15% / h of the reactor volume, the flow rate of the sodium hydroxide solution is 6.0% / h of the reactor volume, and the flow rate of the ammonia solution is 0.45% / h of the reactor volume;
[0199] In step ②, the reaction time of the pH drop period is 15 hours, the pH value decrease rate in the pH drop period is 0.05-0.15 / h, and the reaction time of the pH plateau period is 33 hours;
[0200] During the coprecipitation reaction, when the upper limit of the reactor volume is reached, concentration begins, and the rest remain unchanged;
[0201] A positive electrode material precursor is prepared.
[0202] Example 9
[0203] Prepare a chemical formula Ni 0.50 Co 0.10 Mn 0.40 (OH) 2 , a positive electrode material precursor with a particle size D50 of 7.2μm.
[0204] This embodiment is carried out in a similar manner to that of Embodiment 1, except that:
[0205] In step ①, the pH of the base solution is controlled to be 11.00;
[0206] In step ②, the reaction time of the pH drop period is 20 hours, the pH value decrease rate in the pH drop period is 0.03-0.07 / h, and the reaction time of the pH plateau period is 37 hours;
[0207] During the coprecipitation reaction, when the upper limit of the reactor volume is reached, concentration begins, and the rest remain unchanged;
[0208] A positive electrode material precursor is prepared.
[0209] Example 10
[0210] Prepare a chemical formula Ni 0.50 Co 0.10 Mn 0.40 (OH) 2 , a positive electrode material precursor with a particle size D50 of 3.5μm.
[0211] This embodiment is carried out in a similar manner to that of Embodiment 1, except that:
[0212] In step ①, the mass concentration of ammonia water in the bottom liquid is controlled to be 5.0 g / L; the flow rates of the metal salt and the sodium hydroxide solution remain unchanged, and the flow rate of the ammonia water solution is 0.30% / h of the reactor volume, and a coprecipitation reaction is performed to obtain a slurry;
[0213] In step ②, the reaction time of the pH drop period is 15 hours, the pH value decrease rate in the pH drop period is 0.05-0.15 / h, and the reaction time of the pH plateau period is 26 hours;
[0214] The mass concentration of ammonia water during the coprecipitation reaction was 5.0 g / L;
[0215] During the coprecipitation reaction, when the upper limit of the reactor volume is reached, concentration begins, and the rest remain unchanged;
[0216] A positive electrode material precursor is prepared.
[0217] Embodiment 11
[0218] Prepare a chemical formula Ni 0.50 Co 0.10 Mn 0.40 (OH) 2 , a positive electrode material precursor with a particle size D50 of 3.1μm.
[0219] This embodiment is carried out in a similar manner to that of Embodiment 1, except that:
[0220] In step ①, the mass concentration of ammonia water in the bottom liquid is controlled to be 13.5 g / L; the flow rates of the metal salt and the sodium hydroxide solution remain unchanged, and the flow rate of the ammonia water solution is 0.80% / h of the volume of the reactor, and a coprecipitation reaction is performed to obtain a slurry;
[0221] The actual pH value during the coprecipitation reaction was controlled so that the pH value gradually decreased from 11.50 (pH decline period) to 10.50 and remained unchanged (pH plateau period);
[0222] In step ②, the reaction time of the pH drop period is 15 hours, the pH value decrease rate in the pH drop period is 0.05-0.15 / h, and the reaction time of the pH plateau period is 22 hours;
[0223] The mass concentration of ammonia water during the coprecipitation reaction was 13.5 g / L;
[0224] During the coprecipitation reaction, when the upper limit of the reactor volume is reached, concentration begins, and the rest remain unchanged;
[0225] A positive electrode material precursor is prepared.
[0226] Example 12
[0227] Prepare a chemical formula Ni 0.50 Co 0.10 Mn 0.40 (OH) 2 , a positive electrode material precursor with a particle size D50 of 3.5μm.
[0228] This embodiment is carried out in a similar manner to that of Embodiment 1, except that:
[0229] In step ①, the pH of the bottom liquid is controlled to be 12.00, and the mass concentration of ammonia water in the bottom liquid is 10.5 g / L; the flow rates of the metal salt and the sodium hydroxide solution remain unchanged, and the flow rate of the ammonia water solution is adjusted to 0.63% / h of the volume of the reactor, and a coprecipitation reaction is performed to obtain a slurry;
[0230] In step ②, the actual pH value of the coprecipitation reaction process is controlled so that the pH value is gradually reduced from 12.00 to 10.50 and maintained unchanged;
[0231] The reaction time of pH drop period was 30h, the pH value decrease rate in pH drop period was 0.03-0.07 / h, and the reaction time of pH plateau period was 39h;
[0232] The mass concentration of ammonia water during the coprecipitation reaction was 10.5 g / L;
[0233] During the coprecipitation reaction, when the upper limit of the reactor volume is reached, concentration begins, and the rest remain unchanged;
[0234] Prepare the positive electrode material precursor (its CP diagram is as follows Figure 7 shown).
[0235] pass Figure 7 It can be seen that in the positive electrode material precursor prepared in Example 12, the core layer of the secondary particles is distributed in a network shape, and the shell layer is distributed in a radial shape.
[0236] Embodiment 13
[0237] Prepare a chemical formula Ni 0.50 Co 0.10 Mn 0.40 (OH) 2, a positive electrode material precursor with a particle size D50 of 3.2μm.
[0238] This embodiment is carried out in a similar manner to that of Embodiment 1, except that:
[0239] In step ①, the pH of the bottom liquid is controlled to be 10.50, the mass concentration of ammonia water in the bottom liquid is 8.0 g / L, the flow rates of the metal salt and sodium hydroxide solution remain unchanged, and the flow rate of the ammonia water solution is 0.48% / h of the volume of the reactor, and a coprecipitation reaction is performed to obtain a slurry;
[0240] In step ②, the actual pH value of the coprecipitation reaction process is controlled so that the pH value is gradually reduced from 10.50 to 10.00 and maintained unchanged;
[0241] The reaction time of pH drop period was 15h, the pH value decrease rate in pH drop period was 0.03-0.05 / h, and the reaction time of pH plateau period was 22h;
[0242] The mass concentration of ammonia water during the coprecipitation reaction was 8.0 g / L;
[0243] During the coprecipitation reaction, when the upper limit of the reactor volume is reached, concentration begins, and the rest remain unchanged;
[0244] A positive electrode material precursor is prepared.
[0245] Embodiment 14
[0246] Prepare a chemical formula Ni 0.85 Co 0.05 Mn 0.10 (OH) 2 , a positive electrode material precursor with a particle size D50 of 3.6μm.
[0247] This embodiment is carried out in a similar manner to that of Embodiment 1, except that:
[0248] In step ①, the molar ratio of Ni:Co:Mn in the metal salt solution is 85.0:5.0:10.0;
[0249] In step ②, the reaction time of the pH drop period is 15 hours, the pH value decrease rate in the pH drop period is 0.05-0.15 / h, and the reaction time of the pH plateau period is 25 hours;
[0250] During the co-precipitation reaction, when the upper limit of the reactor volume is reached, concentration begins, and the rest remain unchanged to prepare a positive electrode material precursor.
[0251] Comparative Example 1
[0252] Prepare a chemical formula Ni 0.50 Co0.10 Mn 0.40 (OH) 2 , a positive electrode material precursor with a particle size D50 of 3.1μm.
[0253] This embodiment is carried out in a similar manner to that of Embodiment 1, except that:
[0254] In step ①, the pH of the base solution is controlled to be 12.00;
[0255] In step ②, the actual pH value of the coprecipitation reaction process is controlled so that the pH value is gradually reduced from 12.00 to 10.50 and maintained unchanged;
[0256] The reaction time of pH drop period was 30h, the pH value decrease rate in pH drop period was 0.05-0.10 / h, and the reaction time of pH plateau period was 37h;
[0257] During the coprecipitation reaction, when the upper limit of the reactor volume is reached, concentration begins, and the rest remain unchanged;
[0258] A positive electrode material precursor is prepared.
[0259] Comparative Example 2
[0260] Prepare a chemical formula Ni 0.50 Co 0.10 Mn 0.40 (OH) 2 , a positive electrode material precursor with a particle size D50 of 3.7μm.
[0261] This embodiment is carried out in a similar manner to that of Embodiment 1, except that:
[0262] In step ①, the mass concentration of ammonia water in the base liquid is controlled to be 8.0 g / L; the flow rates of the metal salt and the sodium hydroxide solution remain unchanged, the flow rate of the ammonia water solution is 0.48% / h of the reactor volume, and a coprecipitation reaction is carried out to obtain a slurry.
[0263] In step ②, the reaction time of the pH drop period is 15 hours, the pH value decrease rate in the pH drop period is 0.05-0.15 / h, and the reaction time of the pH plateau period is 27 hours;
[0264] The mass concentration of ammonia water during the coprecipitation reaction was 8.0 g / L;
[0265] During the coprecipitation reaction, when the upper limit of the reactor volume is reached, concentration begins, and the rest remain unchanged;
[0266] A positive electrode material precursor is prepared.
[0267] Table 1: Summary of reaction conditions of examples and comparative examples
[0268]
[0269] Test Example 1
[0270] The positive electrode material precursor prepared in the above example was subjected to physical and chemical data testing, and the test results are shown in Table 1; specifically:
[0271] 1. Reference standard GB / T 19077-2016; Malvern 3000 laser particle size analyzer is used to test the particle size D50;
[0272] 2. Refer to GB / T 19077-2016 standard, use Malvern 3000 laser particle size analyzer to test the particle size D1. After the sample is tested, the pre-pressure D1 is obtained. 1t pressure is used, 0.5g is injected at a time, and the cross-sectional area of the sample is 1.298cm 2 After being treated in the pressure tower, the particle size is tested by sampling to obtain the D1 after compression. The fragmentation rate (D) = (D1 before compression - D1 after compression) / D1 before compression.
[0273] It should be noted that the particle size D1 in the present invention is the particle size corresponding to when the cumulative particle size distribution percentage of the positive electrode material precursor reaches 1%.
[0274] Table 2 Structural parameters of the positive electrode material precursors prepared in the examples and comparative examples
[0275]
[0276] Test Example 2
[0277] Preparation of positive electrode materials for lithium-ion batteries:
[0278] The positive electrode material precursor prepared in the above example and LiOH were mixed uniformly in a molar ratio of 1:1.05 by a high-speed mixer to obtain a mixture;
[0279] The mixed material is sintered in a box furnace under air atmosphere (heating to 850° C. at a heating rate of 5° C. / h for 12 h), and the sintered material is cooled, crushed and sieved in sequence to obtain the lithium-ion battery positive electrode material.
[0280] Preparation of lithium-ion batteries:
[0281] (1) The above-mentioned lithium-ion battery positive electrode material, conductive carbon black, and binder PVDF (polyvinylidene fluoride) are mixed into a slurry at a ratio of 8:1:1, and the slurry is evenly coated on an aluminum foil with a length and width of 2 cm×1 cm to prepare a positive electrode sheet;
[0282] (2) Assemble the battery case, positive electrode sheet, negative electrode sheet (metal lithium sheet), diaphragm, spring, and electrolyte gasket into a button battery in a vacuum glove box.
[0283] The discharge capacity of the prepared lithium-ion battery (2.8-4.5V / 0.2C, 1C = 200mAh g -1 ) and cycle retention rate (@2.8-4.5V / 0.5C / / 500 cycles) were tested at a test temperature of 25°C±1°C and a humidity of <40%. The results are shown in Table 3.
[0284] Table 3 Electrical properties of positive electrode materials prepared from precursors of the examples and comparative examples
[0285] Serial number Discharge capacity (mAh / g) Cycle retention rate (%) Example 1 211.6 85.9 Example 2 209.8 83.2 Example 3 208.7 84.7 Example 4 212.9 86.4 Example 5 206.2 88.2 Example 6 205.7 85.4 Example 7 206.8 84.1 Example 8 207.6 80.4 Example 9 210.5 81.6 Example 10 187.2 82.4 Embodiment 11 193.5 80.3 Example 12 182.4 76.3 Embodiment 13 188.2 71.2 Embodiment 14 203.6 72.3 Comparative Example 1 170.5 62.7 Comparative Example 2 175.2 65.3
[0286] From the above results, it can be analyzed that the aspect ratio of the primary particles in the secondary particle shell and the aspect ratio of the primary particles on the secondary particle surface have a synergistic effect. Both have a great influence on the particle strength of the positive electrode material precursor, the discharge capacity and capacity retention rate of the lithium-ion battery. The primary particles with appropriate aspect ratios in the secondary particle shell and the secondary particle surface are more conducive to the positive electrode material precursor to exert higher capacity and cycle performance. The specific analysis is as follows:
[0287] Examples 1 to 4 and Examples 7 to 9 all prepared positive electrode material precursors with an internal mesh and external radial structure, with a particle aspect ratio ranging from 2.8 to 6.0, an outer layer thickness / radius ranging from 0.61 to 0.84, and an inner layer porosity ranging from 6.5 to 10.4%. At the same time, they have a medium nickel ratio (Ni 40-70%) and a particle size range of 2.5 to 8 μm, and have a high particle strength, discharge capacity, and good cycle performance as a whole. The specific reasons are as follows: The internal mesh and external radial structure, when having a certain outer layer thickness / radius value, particle aspect ratio, and inner layer porosity, will make the positive electrode have a better Li + Migration kinetics, better internal and external kinetic balance and stronger particle strength can reduce Li + Diffusion resistance and release of internal stress ultimately manifest themselves in higher discharge capacity and cycle retention rate.
[0288] Examples 5 to 6 prepared two metal element (W / Al) doped positive electrode material precursors having the structure and physicochemical index characteristics of the present invention, which demonstrated excellent performance in both discharge capacity and cycle retention rate, indicating that metal element doping is also applicable when having the structure and physicochemical index characteristics of the present invention.
[0289] The cathode material precursor prepared in Comparative Example 1 is basically consistent with Example 1 in other indicators except that the aspect ratio of the primary particles on the surface is larger. The particle strength, discharge capacity and cycle retention rate are all lower than those in Example 1, especially the capacity and cycle performance, indicating that the appropriate aspect ratio of the primary particles on the surface is beneficial to the particle strength, so that the material as a whole has higher capacity and cycle performance.
[0290] The positive electrode material precursor prepared in Comparative Example 2 is basically the same as Example 1 except that the particle aspect ratio is larger. The particle strength, discharge capacity, and cycle retention rate are all lower than those in Example 1, especially the capacity and cycle performance. Specifically, compared with Example 1, the particle aspect ratio of Comparative Example 2 is 8.1, which is significantly higher than 4.1 of Example 1. The material with too large primary particle aspect ratio has more grain boundaries and poor particle strength, which is not good for both capacity and cycle performance. Therefore, the appropriate external particle aspect ratio is conducive to reducing the resistance to Li+ diffusion and improving particle strength, so that the positive electrode material has both higher capacity and better cycle performance.
[0291] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A cathode material precursor, characterized in that: The positive electrode material precursor includes secondary particles composed of primary particles, the secondary particles include a core layer and a shell layer, in the cross section of the secondary particles, the average aspect ratio of the shell layer primary particles is (1.5-8):1, and in the surface of the secondary particles, the average aspect ratio of the primary particles is (1-3):
1.
2. The cathode material precursor according to claim 1, characterized in that: The ratio of the thickness of the shell layer in the secondary particles to the radius of the secondary particles is 0.55 to 0.
95.
3. The cathode material precursor according to claim 1, characterized in that: The core layer of the secondary particles is distributed in a reticular shape, and the shell layer is distributed in a radial shape; And / or, the porosity of the core layer in the secondary particles is 4-14%.
4. The cathode material precursor according to claim 1, characterized in that: The chemical formula of the positive electrode material precursor is Ni x Co y Mn z M t (OH)2, wherein 0.4≤x<1, 0≤y≤0.2, 0.2≤z≤0.6, 0≤t≤0.05, x+y+z+t=1, and M is selected from at least one of W, Al, Zr, Si, Mg, Mo, B, Sr and Ta.
5. The cathode material precursor according to any one of claims 1 to 4, characterized in that: The positive electrode material precursor meets one or more of the following conditions: a. In the cross section of the secondary particles, the average aspect ratio of the shell primary particles is (2 to 6): 1; b. In the surface of the secondary particles, the average aspect ratio of the primary particles is (1.05-2.1):1; c. The ratio of the thickness of the shell layer in the secondary particles to the radius of the secondary particles is 0.6 to 0.9; d. The porosity of the core layer of the secondary particles is 5-12%; e. The chemical formula of the positive electrode material precursor is Ni x Co y Mn z M t (OH)2, where, 0.4≤x≤0.7, 0≤y≤0.2, 0.2≤z≤0.6, 0≤t≤0.05, x+y+z+t=1; f. The particle size D50 of the positive electrode material precursor is 2-15 μm, preferably 3-7 μm.
6. A method for preparing a cathode material precursor according to any one of claims 1 to 5, characterized in that: The preparation method comprises the following steps: preparing a metal salt solution, a complexing agent solution and a precipitant solution; mixing the complexing agent solution, the precipitant solution and water to form a base solution; Under the protection of inert gas, the metal salt solution, the complexing agent solution and the precipitant solution are introduced into the base liquid to carry out a coprecipitation reaction.
7. The preparation method according to claim 6, characterized in that: The preparation method meets one or more of the following conditions: A: the metal salt solution is selected from one or more of a nickel sulfate solution, a cobalt sulfate solution, a manganese sulfate solution and a salt solution of a doping element M; B: The mass concentration of metal ions in the metal salt solution is 100 to 140 g / L, preferably 110 to 130 g / L, and more preferably 120 g / L; C: The complexing agent solution is selected from an ammonia solution, and preferably, the mass fraction of the complexing agent solution is 0.1%-30%; D: The precipitant solution is selected from sodium hydroxide solution, and preferably, the mass fraction of the precipitant solution is 10%-30%; E: the pH value of the base liquid is 10.5-12.0, and / or the mass concentration of ammonia water in the base liquid is 5-13.5 g / L; F: The pH value of the coprecipitation reaction sequentially experiences a pH drop phase and a pH plateau phase; G: The reaction time of the coprecipitation reaction in the pH drop period is 15-30 hours; H: the pH value of the pH plateau phase is 10.0-10.5, and / or the reaction time of the coprecipitation reaction in the pH plateau phase is 22-39 hours; I: The stirring speed of the coprecipitation reaction is 300-600 r / min, and / or the temperature of the coprecipitation reaction is 55-75° C., and / or the mass concentration of ammonia water in the coprecipitation reaction is 5-13.5 g / L.
8. A positive electrode material for a lithium ion battery, characterized in that: The raw material of the lithium-ion battery positive electrode material includes the positive electrode material precursor according to any one of claims 1 to 5.
9. A lithium ion battery, characterized in that: Comprising the lithium-ion battery positive electrode material as claimed in claim 8.
10. An electrical equipment, characterized in that: Comprising the lithium ion battery as claimed in claim 9.
Citation Information
Cited By
Ternary polycrystalline positive electrode material and preparation method thereof
CN121331785A
A ternary polycrystalline positive electrode material and a preparation method thereof
CN121331785B